33.8k views
11 votes
Use the Multiplication Law of Exponents to explain why 5^3*5^-3 = 1
(URGENT PLEASE)

2 Answers

1 vote

The multiplication law states that

  • a^m×a^n=a^m+n

So

  • 5³×5-³=1
  • 5^(3-3)=1
  • 5⁰=1
  • 1=1
User Tom Sun
by
6.2k points
11 votes

Answer:

1 = 1

Explanation:

  • 5^3*5^-3 = 1

We all know the law of exponents,the one we'll use to solve this is the multiplication law:

  • x^y * x^z = x^y+z
  • If the bases are equal or two numbers then the powers are equal too.

Solved:


  • 5^3 \: * \: 5^(-3) = 1

  • 5 {}^(3 + ( - 3)) = 1

  • 5 ^(0) = 1

x^0 = 1


  • 1 = 1 \: ( \rm \: Proved)

Alternate method:

  • 5^3*5^-3 = 1
  • 5^3*1/5^3 = 1

5^3 and 5^3 cancels, which results to

  • 1 = 1
User Salih Karagoz
by
5.4k points